Streptokinase After Spinal Anaesthesia. A Case Report - Mohamed, Rozilah @ Abdul Hadi; Mat Nor, Mohd Basri; Osman, Ariff (International Islamic University Malaysia, 2006)
The use of thrombolytic agent e.g. streptokinase is indicated in patients with early acute ST elevation myocardial infarction (MI) (if there are no contraindications) is becoming increasingly routine. Its use is however significantly limited by bleeding complications. Spinal epidural haematoma (SEH) is haemorrhage in the spinal epidural space after spinal anaesthesia. SEH may be acute or chronic,spontaneous, posttraumatic, or iatrogenic but its occurrence appears to be particularly associated with acquired coagulopathy from medications and disease states. Patients usually present with acute axial spine pain and evolving focal neurological deficits. With increasing number of available anticoagulants and patient receiving them, anaesthesiologists today have to face the challenge ofbalancing between risks and benefits of regional anesthesia in patients under such medications. The treatment of this condition involves the principles of conservative follow-up directed by an improving examination and an understanding of thepathophysiology of coagulopathy-induced spontaneous epidural bleeds. When thediagnosis is accomplished rapidly, surgical decompression can result in full functional recovery.